Olivine-LiNiPO4 Thin Films: Chemical Compatibility with Liquid Electrolyte and Interface Stability at High Potential. Issue 4 (30th January 2018) - Cherkashinin, Gennady; Eilhardt, Robert; Lebedev, Mikhail V.; Nappini, Silvia; Magnano, Elena; Jaegermann, Wolfram
Abstract : The chemical compatibility between carbon free olivine-LiNiPO4 thin films used as cathode material and LiPF6 /DMC/FEC/0.2%-TMB liquid electrolyte was studied by soft-photoelectron spectroscopy, Ni L- and O K- XANES combined with electrochemical experiments. The stability of the electrolyte-electrode interface at a high charging potential strongly depends on the temperature of LiNiPO4 preparation. For the films grown at 740°C, the chemical composition of the interface is not changed even at a charging potential of 5.2 V, whereas the electrolyte-electrode interface of LiNiPO4 grown at lower temperatures (675°C) decomposes at 5.1 V, involving the cathode material in the chemical reaction.